IoT Based Underwater Robot for Water Quality Monitoring. Issue 1 (January 2021) - Gupta, S; Kohli, M; Kumar, R; Bandral, S
Abstract: With the rising population in India, an increase in requirement of fresh water for agricultural, industrial and other purposes is being witnessed. As such fresh water management has become the need of the hour. In this model automated evaluation of water quality such as its ph value, turbidity and temperature is done. For underwater communication, ESP32 is being used because of its inbuilt Wi-Fi and low power consumption. Machine to Machine communication (i.e. devices communicating with each other and accordingly processing the data efficiently), pH sensor and turbidity meter have been integrated in developing this IoT based project. Adding to this, machine understanding algorithm using K Means has been used in analyzing the water quality based on predefined standards. This project has been developed as a small prototype consisting of low-cost embedded devices such as ESP32, Arduino Uno.